Materialism and compulsive buying of online market user - Naurah Nazifah; Gesit Thabrani (Operations Management and Information System Studies, 2023)
This study aims to analyze the effect of materialism on compulsive buying with buy now pay later and impulsive buying as a mediation variable in college students in Padang City. The number of samples in this study was 294 respondents. Data was collected by distributing questionnaires online and data processing was carried out using the SmartPLS software. The results of this study indicate that (1) Materialism has a positive and significant effect on the use of paylater. (2) Materialism has a positive and significant effect on impulsive buying. (3) Materialism has a positive and significant effect on compulsive buying. (4) Paylater has a positive and significant effect on impulsive purchases. (5) Paylater has a positive and significant effect on compulsive buying. (6) Impulse buying has a positive and significant effect on compulsive buying. (7) Materialism has a positive and significant effect on compulsive buying with the use of paylater as mediation. (8) Materialism has a positive and significant effect on impulsive buying with the use of paylater as mediation. (9) Materialism has a positive and significant effect on compulsive buying with impulsive buying as mediation. (10) Paylater has a positive and significant effect on compulsive buying with impulsive buying as mediation.